2006
DOI: 10.1590/s0004-27302006000500011
|View full text |Cite
|
Sign up to set email alerts
|

Transtorno da compulsão alimentar periódica em uma população de obesos mórbidos candidatos a cirurgia bariátrica do Hospital Universitário Oswaldo Cruz, em Recife - PE

Abstract: RESUMOObjetivos: Avaliar a freqüência de transtorno da compulsão alimentar periódica (TCAP) e dos principais transtornos psiquiátricos associados à obesidade mórbida em indivíduos à espera de cirurgia bariátrica. To analyze the frequency of binge eating disorder (BED) and of the main psychiatric disorders associated with morbid obesity in individuals on the waiting list for bariatric surgery. Method: Cross sectional study. Interviews with patients from the Surgery for Obesity Program of Oswaldo Cruz University… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
30
1
19

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(57 citation statements)
references
References 29 publications
7
30
1
19
Order By: Relevance
“…These results are similar to those of a previous study 29 conducted with morbidly obese patients, which observed an overall BED prevalence of 56.7%, namely 25.4% with moderate binging and 31.3% with severe binging. In turn, higher rates of BED have been reported for patients seeking weight loss treatment, 30 which is compatible with the characteristics of our sample.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…These results are similar to those of a previous study 29 conducted with morbidly obese patients, which observed an overall BED prevalence of 56.7%, namely 25.4% with moderate binging and 31.3% with severe binging. In turn, higher rates of BED have been reported for patients seeking weight loss treatment, 30 which is compatible with the characteristics of our sample.…”
Section: Discussionsupporting
confidence: 91%
“…Similar results have been reported in a previous study designed to assess the prevalence of psychiatric disorders according to the presence of absence of BED in morbidly obese patients. 29 In that study, the group with BED showed a high prevalence of major depression (42.1%), with a significant difference (p = 0.001) between patients with and without the disorder. 29 Another study 31 carried out with obese patients enrolled in weight loss programs found an association between depression and a higher chance of having BED (57%) when compared with patients without depression (21%), also at a statistically significant difference (p = 0.001).…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…In the general population, the prevalence of BED is of 2-3%. In Brazil, a prevalence of 15-22% has been reported in patients that look for help for weight loss 18 .…”
Section: Abstract: Obesity; Fto; Satietymentioning
confidence: 99%
“…In the general population, the prevalence of BED is of 2-3%. In Brazil, a prevalence of 15-22% has been reported in patients that look for help for weight loss 18 .Due to its expression in the hypothalamus, FTO may be associated with satiety modulation and, consequently play a role in the genesis of BED, contributing to severe obesity and its complications.This article sought to report the current knowledge on the association of polymorphisms of FTO with satiety in obese individuals. …”
mentioning
confidence: 99%